Fiscal Multipliers and Foreign Holdings of Public Debt. (9th September 2021) - Broner, Fernando; Clancy, Daragh; Erce, Aitor; Martin, Alberto
Abstract: This article explores a natural connection between fiscal multipliers and foreign holdings of public debt. Although fiscal expansions can raise domestic economic activity through various channels, they can also have crowding-out effects if the resources used to acquire public debt reduce domestic consumption and investment. These crowding-out effects are likely to be weaker when governments have access to foreign savings when selling their debt, leading to larger fiscal multipliers. We test this hypothesis for the U.S. in the post-war period and for a panel of 17 advanced economies from the 1980s to the present. To do so, we assemble a novel database of public debt holdings by domestic and foreign creditors for these countries. We combine these data with standard measures of fiscal policy shocks and show that, indeed, the size of fiscal multipliers is increasing in the share of public debt held by foreigners. In particular, the fiscal multiplier is smaller than one when the foreign share is low, such as in the U.S. in the 1950s and 1960s and Japan today, and larger than one when the foreign share is high, such as in the U.S. and several European countries today.